2016
DOI: 10.1007/s11573-016-0828-2
|View full text |Cite
|
Sign up to set email alerts
|

“Whom do I want to be the next CEO?” Desirable successor attributes in family firms

Abstract: The aim of our study is to understand whether different incumbent attitudes towards desirable successor attributes have an impact on their intention to nominate a family member or a non-family member as CEO and the extent to which this intention is moderated by the number of family members working in the firm as a proxy of socioemotional wealth preservation. Our main findings suggest that an incumbent's intention to nominate a family member as the next CEO increases when they believe family standing attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
0
25
0
1
Order By: Relevance
“…Family blockholders are willing to exert their authority over firm strategy, act altruistically toward their family members, implement nepotism as a dominant culture, and create family dynasties through management succession (Astrachan, 2010;Firfiray, Cruz, Neacsu, & Gómez-Mejía, 2017;Handler, 1994;Schulze, Lubatkin, & Dino, 2003), among other actions accentuating family management entrenchment. As a result, family firms differ substantially from nonfamily firms regarding CEO successor intention (Basco & Calabrò, 2017), management development (e.g., Griffeth, Allen, & Barrett, 2006), and workplace justice perceptions ( Van der, Blondel, & Carlock, 2005), among other human resource issues. Family owners promote behavior and values undermining firm human resources, 6 such as entitlement (Aronoff, 2004;Schulze et al, 2003), preferential or asymmetric treatment (e.g., bifurcation bias, Daspit et al, 2018;Jennings, Dempsey, & James, 2017), and parental altruism (Lubatkin, Schulze, Ling, & Dino, 2005;Schulze, Lubatkin, & Dino, 2002).…”
Section: Training and Development As A Mediator Of Family Firms Andmentioning
confidence: 99%
“…Family blockholders are willing to exert their authority over firm strategy, act altruistically toward their family members, implement nepotism as a dominant culture, and create family dynasties through management succession (Astrachan, 2010;Firfiray, Cruz, Neacsu, & Gómez-Mejía, 2017;Handler, 1994;Schulze, Lubatkin, & Dino, 2003), among other actions accentuating family management entrenchment. As a result, family firms differ substantially from nonfamily firms regarding CEO successor intention (Basco & Calabrò, 2017), management development (e.g., Griffeth, Allen, & Barrett, 2006), and workplace justice perceptions ( Van der, Blondel, & Carlock, 2005), among other human resource issues. Family owners promote behavior and values undermining firm human resources, 6 such as entitlement (Aronoff, 2004;Schulze et al, 2003), preferential or asymmetric treatment (e.g., bifurcation bias, Daspit et al, 2018;Jennings, Dempsey, & James, 2017), and parental altruism (Lubatkin, Schulze, Ling, & Dino, 2005;Schulze, Lubatkin, & Dino, 2002).…”
Section: Training and Development As A Mediator Of Family Firms Andmentioning
confidence: 99%
“…In line with the research stream investigating the antecedents of succession intention at the individual level (e.g., Basco & Calabrò, 2017), we focus on organization-level antecedents—namely, family strategic resources—as drivers of CEO succession intention. Indeed, extant research has shown that resources and resource providers are seen as relevant predictors of family firms’ strategic decisions, such as succession (Davis & Harveston, 1998).…”
Section: Family Strategic Resources and Ceo Succession Intentionmentioning
confidence: 99%
“…However, and in line with the mainstream management literature, scarce attention has been devoted to the presuccession phase (Berns & Klarner, 2017). In particular, the nomination phase, which involves identifying the range of succession candidates and developing the succession intention (Basco & Calabrò, 2017), represents an untapped research area that deserves further attention. In fact, it is during this phase that, often disregarding the idea of an heir apparent, family members develop their intention regarding nominating either a family or a nonfamily member as the next CEO (Le Breton-Miller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo anteriormente señalado, el autor expone la conveniencia de la incorporación de hijos de los fundadores en la empresa de manera laboral con dos años de anticipación al proceso, con el fin de que aprendan las actividades y funcionamiento de la organización (Monsó, 2005). El instrumento utilizado, fue retomado de los autores Basco & Calabrò (2016) conformado por 13 ítems de información demográfica dónde se indaga información tanto de la empresa como del participante para la correcta caracterización de la conformación de las EF de la localidad y nueve preguntas para determinar el nivel de importancia brindado a ciertos elementos considerados determinantes para la elección del sucesor, primero de la dimensión de atributos familiares (AF) con 5 reactivos (orden de nacimiento, edad, parentesco, género y disponibilidad de compartir la propiedad) y; segundo los atributos de competencia administrativa (AA) con cuatro ítems (experiencia y habilidades financieras y de marketing, experiencia laboral externa a la EF y la trayectoria y desempeño profesional) (ver tabla 1), mediante una escala tipo Likert de cinco puntos, los cuales van desde nada importante (uno) hasta muy importante (cinco); los elementos mostraron un nivel de confiabilidad considerable pues el alfa de Cronbach figura con .713. versión 21 para capturar y analizar los datos obtenidos durante el trabajo de campo y posteriormente presentar resultados de la investigación, los cuales se centran en las 52 respuestas obtenidas en las organizaciones de tipo familiar, que suman 47. Éstos mantienen una media de respuesta de 3.468.…”
Section: Proceso De Sucesión En Las Empresas Familiaresunclassified